The Toronto District School Board: A global city school system's structures, processes, and student outcomes (UCL Press, 2016)
In this article we describe the ways that academic opportunity is distributed within the Toronto District School Board (TDSB), Canada's largest and most demographically diverse public education system. By putting a range of recent outcome data into historical, organizational, and policy contexts, we provide a snapshot of how one of North America's largest school systems works in ways that simultaneously reinforce, and challenge, patterns of academic stratification. Although schooling in some global cities is shaped by decentralization, competition, and a 'school reform industry', public education in Toronto is very much characterized by centralization and increased public investment. Therefore, this paper queries whether these larger historical and structural factors lead to greater equity for racialized and minoritized communities. Through the infusion of equity-focused policies and anti-discrimination-centred interventions, can the case be made that marginalized groups are navigating the school system with greater success? Reviewing historical and recent data from the Toronto Board of Education and TDSB, we reflect on and query the extent of disparity that continues to exist, problematizing the disconnect between policy and addressing the root causes of inequality.